2017
DOI: 10.1186/s12885-017-3724-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon ion radiotherapy for 80 years or older patients with hepatocellular carcinoma

Abstract: BackgroundTo evaluate the safety and efficacy of carbon ion radiotherapy (C-ion RT) for 80 years or older patients with hepatocellular carcinoma (HCC).MethodsEligibility criteria of this retrospective study were: 1) HCC confirmed by histology or typical hallmarks of HCC by imaging techniques of four-phase multidetector-row computed tomography or dynamic contrast-enhanced magnetic resonance imaging; 2) no intrahepatic metastasis or distant metastasis; 3) no findings suggesting direct infiltration of the gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Dose constraints were as follows: (1) D 1cc <40 Gy (RBE) administered to the gastrointestinal tract and (2) V 20 <35% administered to the liver. Dose to the portal vein and bile duct was reduced as much as was possible (8). Figure 1 shows a typical radiation field with dose distribution.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Dose constraints were as follows: (1) D 1cc <40 Gy (RBE) administered to the gastrointestinal tract and (2) V 20 <35% administered to the liver. Dose to the portal vein and bile duct was reduced as much as was possible (8). Figure 1 shows a typical radiation field with dose distribution.…”
mentioning
confidence: 99%
“…Numerous local treatment options can be employed for treating HCC, with particle therapy, such as proton beam therapy and carbon ion radiotherapy (C-ion RT), being one of the less-invasive options (7,8). Most patients with HCC have a history of chronic liver disease resulting from alcohol abuse, or infection with hepatitis C or B virus, so that patients with HCC already are in a state of secondary sarcopenia caused by cirrhosis or chronic hepatitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because Gy (RBE) is calculated based on the survival response of human salivary gland cells after C-ion beam irradiation, and not of liver cells, a direct comparison between Gy (RBE) and Gy for the liver can be problematic; moreover, the dose constraints of C-ion RT and those of IMRT for the liver might be different. However, the dose constraints of C-ion RT for the liver used in our study are considered safe, as previous clinical studies of C-ion RT used the same dose constraints, and no severe toxicities were observed [7][8][9][10][11].…”
Section: A Number Of Studies Have Investigated the Relationships Betwmentioning
confidence: 69%
“…Particle therapy has since improved radiation dose distributions further still [5,6]. In particular, carbon ion RT (C-ion RT) has produced favorable clinical outcomes for patients with HCC [7][8][9][10][11], as this modality reduces the dose to the liver while ensuring good target coverage [12,13] owing to its physical characteristics that include distal tail-off because of a high and narrow Bragg Peak as well as a sharp lateral penumbra [14]. Abe et al's dosimetric comparison between C-ion RT and SBRT for HCC treatment found that the former has better sparing of the liver [5].…”
Section: Introductionmentioning
confidence: 99%